Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1002/j.1460-2075.1996.tb00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific initiation and switch to elongation of human immunodeficiency virus type 1 reverse transcription require the post-transcriptional modifications of primer tRNA3Lys.

Abstract: Initiation of RNA‐dependent DNA synthesis by retroviral reverse transcriptases is generally considered as unspecific. In the case of human immunodeficiency virus type 1 (HIV‐1), the natural primer is tRNA3Lys. We recently found evidence of complex interactions between tRNA3Lys and HIV‐1 RNA that may be involved in the priming process. In this study, we compare the ability of natural and unmodified synthetic tRNA3Lys and 18mer oligoribo‐ and oligodeoxyribonucleotides complementary to the viral primer binding si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
261
4
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(292 citation statements)
references
References 35 publications
(21 reference statements)
23
261
4
1
Order By: Relevance
“…5), we speculated that NC nucleic acid chaperone activity may be stabilizing extended interactions between the tRNA primer and the RNA template. We considered the possibility that the interaction between residues in the A-rich loop and the anticodon loop of tRNA 3 Lys promote efficient (Ϫ) SSDNA synthesis (1,9). However, although it has been reported that substitution of the six residues in the A-rich loop (nt 162-167 in HIV-1 MAL; GUAAAA) with five residues (CUAUG) can significantly reduce (Ϫ) SSDNA synthesis in vitro (1), others have shown that deletion of the four A residues in HIV-1 HXB2 RNA leads to synthesis of slightly lower or very similar amounts of (Ϫ) SSDNA over time (4,49,79).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5), we speculated that NC nucleic acid chaperone activity may be stabilizing extended interactions between the tRNA primer and the RNA template. We considered the possibility that the interaction between residues in the A-rich loop and the anticodon loop of tRNA 3 Lys promote efficient (Ϫ) SSDNA synthesis (1,9). However, although it has been reported that substitution of the six residues in the A-rich loop (nt 162-167 in HIV-1 MAL; GUAAAA) with five residues (CUAUG) can significantly reduce (Ϫ) SSDNA synthesis in vitro (1), others have shown that deletion of the four A residues in HIV-1 HXB2 RNA leads to synthesis of slightly lower or very similar amounts of (Ϫ) SSDNA over time (4,49,79).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on HIV-1 initiation in vitro indicate that two modes of synthesis are involved in this process: (i) initiation, characterized by a distributive, slow extension of the primer and a high dissociation rate of reverse transcriptase (RT) from the primer-template complex; and (ii) elongation, which follows a transition between incorporation of the sixth and seventh nt and results in a dramatic increase in the processivity and rate of DNA synthesis (1)(2)(3)(4)(5). The inability of HIV-1 RT to initiate (Ϫ) SSDNA synthesis efficiently in vitro may be in part due to the nature of the three-dimensional structure of the initiation complex, which involves extensive intermolecular interactions between the tRNA 3 Lys primer and the RNA template (see below) (6 -11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction of the tRNA Lys3 anticodon loop with the 6-base A-rich loop at the top of the hairpin on the genomic RNA is believed to be important not for tRNA Lys3 annealing to viral RNA, but for an early pausing in reverse transcription, which has been associated with a transition from low processive initiation to high processive elongation (30)(31)(32). However, although all other lentiviruses use tRNA Lys3 as a primer, and have similar stem/loop structures near the PBS, these do not contain an A-rich loop, and therefore, the stem/loop structure rather than the A-rich loop itself may be the important parameter for inducing this pausing (33).…”
Section: Interactions Between Primer Trna Lys3 and Genomic Rnamentioning
confidence: 99%